BIOLOGICAL SYNTHESIS AND CHARACTERIZATION OF GOLD NANOPARTICLES USING LEMNA MINOR - Saritha, K.; U.Saraswathi; Singaravelu, G.; S.Revathi; V.Jayanthi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Bio molecular synthesis of metal nanoparticles is an intensifying research area due to its impending applications for the development of advanced novel technologies which includes therapeutic and diagnostic devices. Objective: The present study was aimed on the synthesis and characterisation of gold nanoparticles using Lemna minor. Methods: Gold nanoparticles were synthesised using auric chloride and were characterised by UV, XRD, SEM, and TEM analysis. Results: UV spectrum exhibited an absorption peak at 526 nm. X-ray diffraction pattern displayed typical peak of crystalline gold at (111), (200), and (220). The transmission electron microscopy results indicate that the gold nanoparticles were spherical in nature. Conclusion: Environment friendly gold nanoparticles were synthesized by green chemistry using Lemna minor and was characterized by spectroscopy and microscopy Keywords: Lemna minor, gold nanoparticles, Auric chloride.